Plurality in the sphere of the political public - Rincón Covelli, Tatiana (Estudios de Filosofía, 2008)
Attending to the title of this symposium, I want to focus my presentation on the state of the question on some reflections made from philosophy on pluralism in politics and, more specifically, on pluralism in the space or sphere of the political public. To do this, I will assume, here, several questions: first, I will assume that in contemporary societies (of a late modernity or postmodernity) it makes sense to continue talking about different spheres and, specifically, of the public sphere as a sphere other than the sphere private; secondly, I will assume the political public as the space in which common affairs take place, those that interest us as a political community, and with respect to which we converse, deliberate, decide and act in our capacity as political agents or actors; and, thirdly, I will also assume the public-political space as a space for different learning, including moral learning, ethical learning, and political virtue learning. [Fragment]